Resposta morfo adaptativa cutânea e branquial do jundiá (Rhamdia quelen) submetido a diferentes densidades de estocagem e privação alimentar - Scherer, Gabriela Pires (2021)
The world demand for fish has experienced a significant increase in the last decades, mainly due to population growth and the search for consumers for healthier foods. The contribution of aquaculture to world food production has increased significantly in the last few years old. Thus, the need for creation in intensive systems is a constant. However, this system provides stress conditions for fish, and may cause immunosuppression and the development of disease. So the aim of this study was to evaluate the adaptive cutaneous and gill morpho responses of silver catfish submitted to different stocking densities and food deprivation, evaluating its possible effects on the activity of lysozyme in cutaneous mucus, in the population of mucous cells of the skin and gills and determining a collection point more representative on the skin. Silver catfish juveniles (Rhamdia quelen) were distributed in 250L tanks and share into four experimental groups with one control group, that was collected pre-experiment and post-adaptation, the experimental groups were: GDA (high density fed); GDNA (high density not fed); PDA (low density powered); and, PDNA (small density not fed). The values established for small densities were 2.5 kg / m³, while for high densities it was 32 kg / m³. The fishes had 185-195 g, 24-26 cm. The animals in the fed groups received food 2 times a day, with commercial feed being supplied 5% of the biomass of the the tank and the animals in the non-fed group remained fasting during the experiment. After the experimental period, the fish were anesthetized and euthanized to collect biological material. Skin fragments were collected of seven different points on the animal's body, the second left branchial arch and skin mucus samples. In the results, it was observed that the VFNV point is the most representative collection point. The population of mucous cells in the skin was lower in GDNA treatment and higher in PDA. In the gills the cell population mucous membranes was significantly lower in the PDA and PDNA treatments, CONTROL and GDNA were higher. Lysozyme activity of epidermal mucus it was higher in the GDNA treatment than in the other treatments. It was possible to conclude that stocking density and food deprivation offer a stressful situation for specimens of silver catfish, which vary their response to each situation.